Insights into the nanoscale lateral and vertical phase separation in organic bulk heterojunctions via scanning probe microscopy. Issue 6 (26th January 2016) - Chintala, R.; Tait, J. G.; Eyben, P.; Voroshazi, E.; Surana, S.; Fleischmann, C.; Conard, T.; Vandervorst, W.
Abstract : This work demonstrates the feasibility of 3-dimensional characterization of chemical composition with nanometer spatial resolution using a combination of GCIB sputtering and SPM techniques. Abstract : Solution processed polymer (donor) and fullerene (acceptor) bulk heterojunctions are widely used as the photo active layer in organic solar cells. Intimate mixing of these two materials is essential for efficient charge separation and transport. Identifying relative positions of acceptor and donor rich regions in the bulk heterojunction with nanometer scale precision is crucial in understanding intricate details of operation. In this work, a combination of Ar + 2000 gas cluster ion beam and scanning probe microscopy is used to examine the lateral and vertical phase separation within regio-regular poly(3-hexylthiophene)(P3HT):phenyl-C60-butyric acid methyl ester (PCBM) bulk heterojunction. While the Ar + 2000 gas cluster ion beam is used as a sputter tool to expose the underneath layers, scanning probe microscopy techniques are used to obtain two-dimensional (2D) electrical maps (with sub-2 nm lateral resolution). The electrical mapping is decoded to chemical composition, essentially producing lateral and vertical maps of phase separation. Thermal stress causes large PCBM-rich hillocks to form, and consequently affecting the balance of P3HT:PCBM heterojunctions, hence a negative impact on the efficiency of the solar cell. We further developed a method to analyze the efficiency of exciton dissociation based on the current maps and a loss of 20% in efficiency is observed for thermally degraded samples compared to fresh un-annealed samples.